2022
DOI: 10.1002/cac2.12341
|View full text |Cite
|
Sign up to set email alerts
|

PTPRO represses colorectal cancer tumorigenesis and progression by reprogramming fatty acid metabolism

Abstract: Background Abnormal expression of protein tyrosine phosphatases (PTPs) has been reported to be a crucial cause of cancer. As a member of PTPs, protein tyrosine phosphatase receptor type O (PTPRO) has been revealed to play tumor suppressive roles in several cancers, while its roles in colorectal cancer (CRC) remains to be elucidated. Hence, we aimed to explore the roles and mechanisms of PTPRO in CRC initiation and progression. Methods The influences of PTPRO on the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…We next investigated which signaling pathway might contribute to LINC00924-induced PPARα activation. Previous studies outlined a regulatory role for the JNK and ERK and p38 MAPK signaling pathways in regulating PPARα expression [ 23 26 ]. Therefore, we examined protein levels of the JNK, ERK and phosphorylated p38 (p-p38) MAPK in MGC803-NC/LINC00924-OE and AGS-NC/LINC00924-KD cells.…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated which signaling pathway might contribute to LINC00924-induced PPARα activation. Previous studies outlined a regulatory role for the JNK and ERK and p38 MAPK signaling pathways in regulating PPARα expression [ 23 26 ]. Therefore, we examined protein levels of the JNK, ERK and phosphorylated p38 (p-p38) MAPK in MGC803-NC/LINC00924-OE and AGS-NC/LINC00924-KD cells.…”
Section: Resultsmentioning
confidence: 99%
“…Further transcriptome sequencing and KEGG signaling pathway enrichment data showed that the metabolic process in Hep3B cells treated with STA had changed. Growing evidence suggests that metabolic disorder is a significant hallmark of malignant tumors that controls key tumor biological processes such as the proliferation, migration, and invasion of tumor cells ( Dai et al, 2022 ; Sun et al, 2022 ; Tan et al, 2022 ). Thus, by inhibiting the metabolic pathways of tumor cells, the occurrence and development of tumors could be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of PTPs (protein tyrosine phosphatases), PTPRO (protein tyrosine phosphatase receptor type O) has been revealed that PTPRO expression is notably downregulated in CRC liver metastasis compared to the primary cancer, and such a downregulation is associated with poor prognosis of patients with CRC. PTPRO silencing induced the activation of the AKT/mTOR signaling axis, thus promoting de novo lipogenesis by enhancing the expression of SREBP1 and its target lipogenic enzyme ACC1 by activating the AKT/mTOR signaling pathway [69].…”
Section: Pi3k-akt Signaling Pathwaymentioning
confidence: 99%
“…As a member of PTPs, the role of PTPRO in cell signal transduction has attracted more and more attention. It has been proved that PTPRO attenuation is achieved by suppressing PPAR α and its downstream enzyme, peroxidase acyl coenzyme A oxidase 1 (ACOX1), to reduce FA oxidation rate [69]. High expression PPARβ/δ is closely related to the occurrence and development of colorectal cancer.…”
Section: Ppar Signaling Pathwaymentioning
confidence: 99%